Effects of HIV infection on maternal and neonatal health in southern Mozambique: A prospective cohort study after a decade of antiretroviral drugs roll out - González, Raquel (PLoS One, 2017)
INTRODUCTION: The HIV epidemic is concentrated in sub-Saharan Africa. However, limited information exists on its impact on women and infant’s health since the introduction of antiretroviral drugs in this region, where health resources are often scarce. METHODS: The effect of HIV infection on maternal health, birth outcomes and infant health was analysed in two contemporary cohorts of HIV-uninfected and HIV-infected pregnant women from southern Mozambique. Pregnant women attending the first antenatal care visit were followed until one month after delivery. Antiretroviral therapy was administered based on CD4+T cell count and clinical stage. Maternal and neonatal morbidity and mortality, as well as pregnancy outcomes were assessed by mother’s HIV status. RESULTS: A total of 1183 HIV-uninfected and 561 HIV-infected pregnant women were enrolled. HIV-infected women were more likely to have anaemia both at the first antenatal care visit and at delivery than HIV-uninfected women (71.5% versus 54.8% and 49.4% versus 40.6%, respectively, p<0.001). Incidence of hospital admissions during pregnancy was increased among HIV-infected women (RR, 2.04, [95%CI, 1.45; 2.86]; p<0.001). At delivery, 21% of HIV-infected women reported being on antiretroviral therapy, and 70% having received antiretroviral drugs for prevention of mother to child transmission of HIV. The risk of stillbirths was doubled in HIV-infected women (RR, 2.16 [95%CI 1.17; 3.96], p = 0.013). Foetal anaemia was also increased among infants born to HIV-infected women (10.6% versus 7.3%, p = 0.022). No differences were found in mean birth weight, malaria, prematurity and maternal and neonatal deaths between groups. CONCLUSIONS: HIV infection continues to be associated with significant maternal morbidity and poor neonatal health outcomes. Efforts should urgently be made to identify the barriers that impede improvements on the devastating effects of HIV in African women and their infants. TRIAL REGISTRATION: ClinicalTrials.gov NCT 00811421.